Incretin-Based Multi-Agonist Peptides Are Neuroprotective and Anti-Inflammatory in Cellular Models of Neurodegeneration - Katherine O. Kopp; Yazhou Li; Elliot J. Glotfelty; David Tweedie; Nigel H. Greig (Biomolecules, 2024)
Glucagon-like peptide-1 (GLP-1)-based drugs have been approved by the United States Food and Drug Administration (FDA) and are widely used to treat type 2 diabetes mellitus (T2DM) and obesity. More recent developments of unimolecular peptides targeting multiple incretin-related receptors (“multi-agonists”), including the glucose-dependent insulinotropic polypeptide (GIP) receptor (GIPR) and the glucagon (Gcg) receptor (GcgR), have emerged with the aim of enhancing drug benefits. In this study, we utilized human and mouse microglial cell lines, HMC3 and IMG, respectively, together with the human neuroblastoma SH-SY5Y cell line as cellular models of neurodegeneration. Using these cell lines, we studied the neuroprotective and anti-inflammatory capacity of several multi-agonists in comparison with a single GLP-1 receptor (GLP-1R) agonist, exendin-4. Our data demonstrate that the two selected GLP-1R/GIPR dual agonists and a GLP-1R/GIPR/GcgR triple agonist not only have neurotrophic and neuroprotective effects but also have anti-neuroinflammatory properties, as indicated by the decreased microglial cyclooxygenase 2 (COX2) expression, nitrite production, and pro-inflammatory cytokine release. In addition, our results indicate that these multi-agonists have the potential to outperform commercially available single GLP-1R agonists in neurodegenerative disease treatment.